2017
DOI: 10.1155/2017/1621629
|View full text |Cite
|
Sign up to set email alerts
|

AAV-KLF7 Promotes Descending Propriospinal Neuron Axonal Plasticity after Spinal Cord Injury

Abstract: DPSN axons mediate and maintain a variety of normal spinal functions. Unsurprisingly, DPSN tracts have been shown to mediate functional recovery following SCI. KLF7 could contribute to CST axon plasticity after spinal cord injury. In the present study, we assessed whether KLF7 could effectively promote DPSN axon regeneration and synapse formation following SCI. An AAV-KLF7 construct was used to overexpress KLF7. In vitro, KLF7 and target proteins were successfully elevated and axonal outgrowth was enhanced. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…In our recent study, BMSCs engineered to overexpress Krüppel-like Factor 7 (KLF7) improved axon regeneration and repair of the injured nerve when injected into an ANA for engraftment into the injured nerve 3 and KLF7 also promotes such benefits in central nervous system injury. [34][35][36] Prior to this, we found that Schwann cells transfected to over express KLF7, and KLF7 in general, also imparted benefits for successful repair and regeneration of the sciatic nerve following engraftment. 34,35 Through our studies, and those of others, the mechanism by which KLF7 promoted these benefits likely involved increased neurotrophic factor expression, growth cone formation, and axonal myelination.…”
Section: Discussionmentioning
confidence: 97%
“…In our recent study, BMSCs engineered to overexpress Krüppel-like Factor 7 (KLF7) improved axon regeneration and repair of the injured nerve when injected into an ANA for engraftment into the injured nerve 3 and KLF7 also promotes such benefits in central nervous system injury. [34][35][36] Prior to this, we found that Schwann cells transfected to over express KLF7, and KLF7 in general, also imparted benefits for successful repair and regeneration of the sciatic nerve following engraftment. 34,35 Through our studies, and those of others, the mechanism by which KLF7 promoted these benefits likely involved increased neurotrophic factor expression, growth cone formation, and axonal myelination.…”
Section: Discussionmentioning
confidence: 97%
“…Current research has shown GAP43 to be a known marker in detecting nerve regeneration (Li et al, ). GAP43 is mainly involved in sprouting and regeneration of mature axons in their phosphorylated form.…”
Section: Discussionmentioning
confidence: 99%
“…Application of BDNF to the left motor cortex after a thoracic over-hemisection in mice caused collateral sprouting of injured CST axons and formation of contacts with propriospinal INs that was accompanied by functional recovery (Vavrek et al, 2006). In another study, the transduction of the transcription factor Kruppel-like factor 7 (KLF7) by an AAV vector above the injury site after a T10 contusion was shown to promote both descending propriospinal axon plasticity and synapse formation after a T10 contusion in adult mice (Li et al, 2017). KLF7 regulates the expression of a number of genes, including the neurotrophin NGF and its receptor TrkA (Caiazzo et al, 2010).…”
Section: Therapeutic Strategies For Sci Utilizing Propriospinal Insmentioning
confidence: 99%